(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is showed the unique professional characteristics of organizing the process of training future sports coaches to resolve conflicts among group members based on an acmeological approach. It elaborates on specific aspects aimed at resolving conflicts arising in the pedagogical process. The development of professional skills in future sports coaches is crucial for fostering effective leadership, conflict resolution, and pedagogical mastery in sports education. This study examines the acmeological approach as a method for enhancing the professional competencies of sports coaches, particularly in managing conflicts among team members. Despite existing research on pedagogical and psychological preparation, there remains a knowledge gap in integrating acmeological principles into coach training programs. This study aims to bridge this gap by analyzing the role of professional knowledge, organizational skills, and conflict resolution strategies in the training process. A qualitative research methodology was applied, incorporating a review of theoretical frameworks, case studies, and expert interviews. The findings highlight that while future sports coaches often demonstrate strong organizational and communicative abilities, they lack high-level professional mastery and structured conflict resolution skills. The results suggest that systematic professional training, practical applications of pedagogical theories, and structured project-based learning can significantly enhance the effectiveness of coach education. The implications of this research emphasize the necessity of integrating acmeological strategies into coach training curricula to ensure sustainable professional growth. Future studies should explore the impact of psychological resilience, leadership development, and modern digital training tools in refining coaching education. A deeper understanding of interpersonal dynamics, motivational strategies, and team management will further contribute to preparing highly competent and adaptive sports coaches.